1993
DOI: 10.1111/j.1151-2916.1993.tb03756.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Study of Na‐Si‐O‐N Oxynitride Glasses

Abstract: The structure and properties of Na-Si-0-N oxynitride glasses have been studied by molecular dynamics calculations using a pair potential of the Busing approximation of the Born-Mayer-Huggins type. Nitrogen atoms bonded to one, two, and three silicon atoms coexist in the glass structure. The mean of the number of silicon atoms bonded to a nitrogen atom ranges from 2.4 to 2.1, decreasing with increasing Na,O content from 15 to 30 mol%. It has been assumed that nitrogen atoms bonded to two or fewer silicon atoms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 20 publications
2
17
0
Order By: Relevance
“…A recent investigation by us of a series of these glasses by solid state NMR 47 indicates accordingly, that for glasses with high X:M ratios, the O and N atoms play similar structural roles, i.e. a predominant fraction of the nitrogen atoms are present as N [1] and N [2] . It may be noted that anomalously high X:M ratios could be a result of the glasses containing significant amounts of isolated X [0] species, i.e.…”
Section: Compoundmentioning
confidence: 95%
See 2 more Smart Citations
“…A recent investigation by us of a series of these glasses by solid state NMR 47 indicates accordingly, that for glasses with high X:M ratios, the O and N atoms play similar structural roles, i.e. a predominant fraction of the nitrogen atoms are present as N [1] and N [2] . It may be noted that anomalously high X:M ratios could be a result of the glasses containing significant amounts of isolated X [0] species, i.e.…”
Section: Compoundmentioning
confidence: 95%
“…Cross-linking of SiX 4 tetrahedra X [1] X [2] X [3] La 5 Concurrently there is an increase in the average connectivity of N and a decrease in the X:M ratios. However, the compositional trends clearly differ between these crystalline compounds and the glasses, which make further comparisons difficult.…”
Section: Compoundmentioning
confidence: 96%
See 1 more Smart Citation
“…15 Oxynitride glass formation occurs in a number of M-Si-O-N and M-Si-Al-O-N systems, where M is a modifying cation such as one of the alkali metals (Li, Na, K), [16][17][18][19] the alkaline earths (Mg, Ca, Ba) 17,[19][20][21][22] or Y and the rare earth lanthanides. 16,20,[23][24][25][26][27] It has been found that addition of nitrogen in the form of Si 3 N 4 promotes glass formation and that the glassforming regions are relatively small. 28 In the case of Mg, glasses comprising 15-28 e/o of Mg and 10-12 e/o of nitrogen have been obtained.…”
Section: Introductionmentioning
confidence: 99%
“…The nitrogen content induces indeed an increase of the atomic packing density. 15,28,29 But, even if high e/o N induce high Poisson's ratio -up to 0.29 for the glass with 42 e/o N -the Poisson's ratio is largely controlled by the cation modifier contents. As the cation modifier content increases, the Poisson ratio increases 15 (almost linearly, from 0.276 for 33.2 e/o Ca to 0.291 for 38.0 e/o Ca).…”
Section: E/o (N Content In E/o = 3[n]/(3[n] + 2[o]) With [N] and [O]mentioning
confidence: 97%